1970
DOI: 10.1136/thx.25.5.568
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of oesophagitis in hiatus hernia patients

Abstract: The incidence of oesophagitis has been determined in 108 patients with sliding hiatus hernias using endoscopic, histological, and radiological criteria. Particular consideration has been given to the relationship between inflammatory disease and clinical symptoms. All the patients were attending a thoracic surgical clinic and the spectrum of disease encountered was fairly severe; over half of the cases had established strictures when first seen. The incidence of oesophagitis based on endoscopic evidence was 76… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

1971
1971
1988
1988

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 13 publications
0
4
0
2
Order By: Relevance
“…It is also recognized that the severity of reflux symptoms, the ease with which reflux occurs, and the degree of oesophagitis are poorly correlated (Tuttle, Bettarello, and Grossman, 1960;Siegel and Hendrix, 1963;Ward, Wright, and Collis, 1970;Woodward, 1970) factors governing their relationships are not understood. Secondary peristalsis induced by a surge of refluxed gastric contents has been considered as a protective mechanism emptying the oesophageal lumen of irritant juices (Creamer, 1955;Nagler and Spiro, 1961).…”
Section: Discussionmentioning
confidence: 99%
“…It is also recognized that the severity of reflux symptoms, the ease with which reflux occurs, and the degree of oesophagitis are poorly correlated (Tuttle, Bettarello, and Grossman, 1960;Siegel and Hendrix, 1963;Ward, Wright, and Collis, 1970;Woodward, 1970) factors governing their relationships are not understood. Secondary peristalsis induced by a surge of refluxed gastric contents has been considered as a protective mechanism emptying the oesophageal lumen of irritant juices (Creamer, 1955;Nagler and Spiro, 1961).…”
Section: Discussionmentioning
confidence: 99%
“…It was not felt justifiable to oesophagoscope the ather asymptomatic patients and absence of oesophagitis is based on subjective evidence alone. Previous experience with hiatus hernia patients, however, has indicated that oesophagitis is nearly always associated with clear-cut symptoms (Ward, Wright, and Collis, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were noted by Woodward (1970), except that he found a poor correlation between prolonged reflux and severity of symptoms. A lack of correlation also between symptoms and oesophagoscopic appearances has previously been shown (Bernstein and Baker, 1958;Tuttle et al, 1960;Siege1 and Hendrix, 1963;Skinner, 1966;Ward et al, 1970). However, appreciable histological oesophagitis may be present without naked eye evidence (Goldberg et af., 1969).…”
Section: The Significance Of Overnight P H Cstimntionsmentioning
confidence: 92%